THE COMPARATIVE ANALYSIS OF SYNTACTIC FEATURES BETWEEN INDONESIAN AND ENGLISH DENOMINAL VERBS - Nugraha, Danang Satria (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
This paper aims to describe the comparison on the syntactic feature of denominal verbs of the Bahasa Indonesia and the English. The syntactic feature defined as a presentation of transitivity (and valency) on the construction of derivated verbs. Based on observation (simak) method formulated by Sudaryanto (2015), the data taken from the usage of Bahasa Indonesia and tha English on written forms. Based on Contrastive Syntax approach designed by Hickey (2017), the result shows two descriptions of comparison, namely the similarities and the differences of syntactic features. First, the similarities are (a) transitive feature and (b) an intransitive feature. Second, the differences are (a) the bitransitive feture of bahasa Indonesia, (b) the markers of transitivity of Bahasa Indonesia and the English and (c) the grammatical relations of the English denominal verb. For further study, researcher may pay attention on detail analysis of the role of denominal verbs in sentences construction of the Bahasa Indonesia and the English.